A real-time decision support system to improve operations in electric bus networks - Ayman Abdelwahed; Pieter L. van den Berg; Tobias Brandt; Wolfgang Ketter (Decision Sciences, 2024)
Electrifying transit bus networks (TBNs) has recently become a challenging problem that many public transport operators around the world are facing. Due to the limited driving range of electric buses, electric TBNs are more sensitive to operational delays and uncertainties. Moreover, the impact on sustainability is most profound when the buses are powered by renewable energy resources, which are often subject to intermittency and uncertainty. In this work, we tackle the complicated problem of planning charging schedules amid these various sources of uncertainty. We develop a real-time decision support system that uses real-time data, predictions, and mathematical optimization to update the charging schedules and mitigate the impact of operational uncertainties. Our results show that the online strategy can maintain higher reliability and renewable energy utilization levels compared to other charging strategies. The study has been carried out in cooperation with the public transport operator in Rotterdam in the Netherlands to assist them in their TBN transition~process.
Keywords: 320; electric transit bus networks; real-time decision support system; renewable energy; smart charging; sustainable public transport